Downlink MIMO-NOMA with and without CSI: A short survey and comparison - Alberto, R.; Monteiro, F. A. (2020 12th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2020)
Non-orthogonal multiple access (NOMA) concatenated with multiple-input multiple-output (MIMO) or with massive MIMO, has been under scrutiny for both broadband and machine-type communications (MTC), even though it has not been adopted in the latest 5G standard (3GPP Release 16), being left for beyond 5G. This paper dwells on the problems causing such cautiousness, and surveys different NOMA proposals for the downlink in cell-centered systems. Because acquiring channel state information at the transmitter (CSIT) may be hard, open-loop operation is an option. However, when users clustering is possible, due to some common statistical CSI, closed-loop operation should be exploited. The paper numerically compares these two operating modes. The users are clustered in beams and then successive interference cancellation (SIC) separates the power-domain NOMA (PD-NOMA) signals at the terminals. In the precoded closed-loop system, the Karhunen-Loève channel decomposition is used assuming that users within a cluster share the same slowly changing spatial correlation matrix. For a comparable number of antennas the two options perform similarly, however, while in the open-loop downlink the number of antennas at the BS is limited in practice, this restriction is waived in the precoded systems, with massive MIMO allowing for a larger number of clusters.